Perceived value of student-led near-peer teaching in anatomy education within a problem-based learning medical curriculum - Serhan, Olivia; Girard, Simon; Sylvestre, Olivier (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2025)
Implication StatementProblem-based learning (PBL) has become widely adopted in medical education, but its implementation presents challenges, particularly regarding decreased anatomy hours and knowledge acquisition compared to traditional methods. The Faculty of Medicine and Health Sciences Anatomy Club's near-peer teaching model demonstrates an effective, scalable solution to bridging anatomical knowledge gaps inherent in PBL curricula. By pairing virtual workshops with clinical cases and interactive quizzes, the club enhances medical students' understanding and retention of anatomy while reducing stress. Survey results suggest significant gains in knowledge and engagement, making this approach beneficial for self-directed, PBL-based settings. Institutions aiming to supplement anatomy education in PBL environments may find this model both feasible and valuable.